MicroRNA‐30d mediated breast cancer invasion, migration, and EMT by targeting KLF11 and activating STAT3 pathway. Issue 10 (19th June 2018) - Han, Mingli; Wang, Yimeng; Guo, Guangcheng; Li, Lin; Dou, Dongwei; Ge, Xin; Lv, Pengwei; Wang, Fang; Gu, Yuanting
Abstract: miR‐30d has been shown to play pivotal roles in cancer development, and has the potential to act as a diagnostic biomarker and therapeutic target in breast cancer. However, the specific function and molecular mechanism of miR‐30d in breast cancer cell growth and metastasis is still unknown. The present study seeks to shed light on the potential contribution of the MiR‐30d‐KLF‐11‐STAT3 pathway in breast cancer. The results revealed that miR‐30d levels were markedly increased in the breast cancer cell lines BT474, MDA‐MB‐231, HCC197, and MDA‐MB‐468 compared with the non‐tumor mammary gland MCF10A cell line. Furthermore, the miR‐30d mimic increased BT474 and MDA‐MB‐231 breast cancer cell survival, inhibited apoptosis and increased Bcl‐2 expression, whilst inhibited Bax protein levels. miR‐30d mimics promote BT474 and MDA‐MB‐231 cell migration, invasion, and mediate the EMT phenotype. However, miR‐30d inhibitors reverse all of the effects of miR‐30d mimics on breast cancer cell biology. Also, we observed that KLF‐11 is a direct target of miR‐30d and KLF‐11 and pSTAT3 expression are determined by miR‐30d. Finally, the results suggest that miR‐30d plays essential roles in breast cancer cells in a manner that is dependent on the levels of KLF‐1 and pSTAT3. In summary, miR‐30d appears to be a novel diagnostic biomarker and treatment target in breast cancer. Abstract : miR‐30d appears to be a novel diagnostic biomarker and treatment target in breast cancer.